ANALISIS PENGELOLAAN OBJEK WISATA SIPINCUR DESA PEARUNG KECAMATAN PARANGINAN KABUPATEN HUMBANG HASUNDUTAN - Nurlinawati Simanjuntak; Try Elnida Manalu; Cinta Napitupulu; Samuel Tambunan; Jelita A. Manalu (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: As an archipelagic nation, Indonesia possesses abundant natural resources, diverse cultures, customs, and religions, which can be utilized in tourism, a key economic sector and the country's second-largest producer after oil and natural gas. Indonesia possesses significant natural resources and cultural heritage, which regions can leverage to increase their own-source revenues through tourism. Since 1978, the government has continuously strived to develop tourism to increase foreign exchange earnings, expand employment opportunities, and promote cultural heritage. Tourism development and development are carried out while maintaining the preservation of national culture and identity. Sipinsur is a tourist attraction located in Pearung Village, Paranginan District, Humbang Hasundutan Regency, North Sumatra Province, with potential for development as a tourist attraction. It boasts beautiful views and cool air. However, it still requires more attention from the local government, management, and, of course, support from the local community. The development of Sipinsur involves tour operators to help promote this attraction, including including it in tour packages. Furthermore, seminars on the potential of the tourist attraction should be held, emphasizing the potential of the attraction through media such as advertisements, videos, and print media such as brochures, booklets, magazines, and other materials. Therefore, good cooperation between the Humbang Hasundutan Regency Government and the management, along with the participation of the local community, is essential to ensure the successful development of the Sipinsur tourist attraction, meeting expectations, and becoming a source of regional income for Humbang Hasundutan Regency and foreign exchange for the country. Keywords: Tourism Object Management   Abstrak: Indonesia sebagai Negara kepulauan memiliki kekayaan alam yang melimpah dengan berbagai kebudayaan, adat, serta agama yang tentunya dapat dimanfaatkan dalam bidang kepariwisataan sebagai sektor yang baik bagi perekonomian dan sebagai penghasil negara kedua setelah minyak bumi dan gas alam. Indonesia ini mempunyai potensi alam dan seni budaya yang cukup besar yang dapat dimanfaatkan oleh daerah untuk meningkatkan pendapatan asli daerah melalui pariwisata. Sejak tahun 1978 pemerintah terus berusaha mengembangkan kepariwisataan dalam meningkatkan penerimaan devisa, memperluas lapangan kerja, dan memperkenalkan kebudayaan. Pembinaan serta pengembangan pariwisata dilakukan dengan tetap memperhatikan terpeliharanya kebudayaan dan kepribadian nasional. Sipinsur adalah salah satu objek wisata yang memiliki potensi untuk dikembangkan sebagai salah satu objek wisata dan menjadi daya tarik wisata yang berada di Desa Pearung Kecamatan Paranginan di Kabupaten Humbang Hasundutan Provinsi Sumatera Utara. Disamping memiliki view yang sangat indah, udara yang sejuk. Namun masih memerlukan perhatian yang lebih dari Pemerintah Daerah, pihak pengelola, dan tentunya dukungan masyarakat setempat. Pengembangan objek wisata objek wisata Sipinsur melibatkan pihak-pihak penyelenggara tour untuk membantu memperkenalkan objek wisata ini, dengan memasukkannya ke dalam sebuah paket wisata. Disamping itu perlu juga diadakan seminar mengenai potensi dengan menitik beratkan terhadap potensi objek wisata tersebut melalui media, seperti iklan, video, dan media cetak seperti brosur, booklet majalah dan lain-lain. Oleh karena itu perlu adanya kerja sama yang baik antara Pemerintah Kabupaten Humbang Hasundutan dengan pihak pengelola, beserta partisipasi masyarakat setempat agar pengembangan objek wisata Sipinsur dapat berjalan dengan baik dan sesuai dengan harapan yang baik dan menjadi sumber pendapatan daerah Kabupaten Humbang Hasundutan dan devisa bagi negara. Kata Kunci: Pengelolaan Objek Wisata